Espectro trófico de Chelonoidis chilensis (Chelonii: testudinidae) en la provincia fitogeográfica del monte (Mendoza, Argentina) - Richard, Enrique (1994)
Between 1983 and 1991, 83 field trips were made to the biogeographical province of Monte, in Mendoza province, Argentina, in order to study the trophic spectrum of Chelonoidis chilensis, among other ecoethological aspects. The trophic period extends from September to April. Adults are herbivorous in strict sense, but this may change according to the available resourees. Trophic spectrum is composed by 14 items (Families) of vegetables. Some items have toxic or potentially toxit substances. Finally, the diet of Ch. chilensis is compared with the one of Ch. donosobarrosi and with other desert tortoises.